Sensory cues and shoppers’ touching behaviour: the case of IKEA - Hultén, Bertil (Henry Stewart Talks, 2013)
Sensory marketing in the 21st century, Mainstream marketing, Retail personalities, Retail environments in practice, Sensory channels, The human senses in theory, The sense of touch, The sense of sight, Design and lighting, The sense of smell, The human senses in practice, Experimental design, Experimental findings, Theoretical implications, Managerial implications
Reviewed at 2017/04/30